(untitled) (FEATURES AND PROBLEMS OF IMPLEMENTING ECONOMIC REFORMS IN AZERBAIJAN, 2025)
As a result of rapidly developing technologies, the continuous growth of the world’s population and increasing living standards, the demand for energy is increasing day by day. Currently, the main share of global energy consumption still belongs to the fossil fuels. However, these fuels play a major role in the deepening of climate change by causing an increase in carbon emissions. The depletion of fossil fuels and their negative ecological effects on the environment are significantly increasing the interest of countries in renewable energy sources. In this context, international energy policies, which seek to ensure energy security as well as environmental sustainability, increasingly identify the promotion of renewable energy sources as a priority direction. Today, renewable energy is accepted by many countries not only as an alternative, but also as a strategic and environmentally necessary energy model. Azerbaijan is also among these countries. This article examines Azerbaijan’s current renewable energy potential and analyzes the strategic importance of these sources in national energy policy. The scientific novelty of the research is that the article serves as a significant information base on the topic in terms of assessing renewable energy sources from an economic perspective and analyzing the development measures implemented in this area in Azerbaijan. The applied significance of the research is the correct determination of the place of renewable sources in the energy policy of Azerbaijan and the provision of scientific and practical contribution to the formation of priority directions in this area.